Lessons from a Blended Learning Implementation – What to do and what not to do? - D., Anitha; D., Kavitha; C., Jeyamala; P, Sharmila (Journal of Engineering Education Transformations, 2025)
Blended learning has taken its importance due to the turbulent ripple in teaching learning process in the past few years. Increase in online teaching expertise among the instructors has paved the way for developing online repositories and thus leading to blended mode offering of courses. But there exists a question “What is the pedagogy for every online repository to be converted to blended learning?” There must be few dos and don’ts in every implementation of any new pedagogical techniques. This research attempts to find a new pedagogical framework for effective implementation of blended learning into the regular curriculum after identifying appropriate learning method. The research is conducted as quantitative research with surveys obtained from students and faculty of the host institution after the first cycle of blended learning implementation in a computer science course. 40 students participated in the learning and recorded their responses through an online survey. Observations from the survey are analyzed in the perspective of different factors of blended learning with statistical analysis and Natural Language Processing (NLP) methods. From the study, it has been inferred that students recognize blended learning as an innovative pedagogical technique provided with factors that motivates and demotivates them. From these observations, suitable recommendations are made in terms of what to do and what not to do and a framework for effective implementation of the blended mode of learning is proposed.